Morphology Selection Kinetics of Li Sphere via Interface Regulation at High Current Density for Pragmatic Li Metal Batteries. Issue 7 (28th December 2021) - Luo, Yang; Li, Tianyu; Yang, Xiaofei; Zhang, Hongzhang; Jia, Ziyang; Yan, Jingwang; Li, Xianfeng
Abstract: Uncontrollable lithium dendrite growth and severe Li/electrolyte side reactions under high operating current densities seriously hinder the development of high‐performance Li metal batteries (LMBs). To address the aforementioned critical issues, spherical Li nuclei are designed via an "all‐in‐one" nitrocellulose (NC)/LiFSI electrolyte to achieve high‐energy/power‐density and long‐cycle LMBs. First, the synergistic effect of LiFSI induced LiF‐rich interface and the nitro group in the NC scaffold promote uniform Li nucleation, resulting in spherical nuclei morphology instead of dendritic even under high current densities. Moreover, NC exhibits strong adsorption energy on the electrode surface, which facilitates the formation of an organic protection layer to suppress side reactions, which enables highly reversible Li cycling, even in a lean‐electrolyte environment. With the assistance of the unique interphase, the Li|Li symmetric cells using NC/LiFSI electrolyte can stably run at a high current density of 10 mA cm ‐2 . Moreover, the assembled Li|LiFePO4 pouch cell achieves excellent cycling stability of 210 cycles with 100% capacity retention. This finding provides a new strategy relying on electrolyte engineering to achieve high‐energy/power‐density and long‐cycling‐life LMBs. Abstract : An "all‐in‐one" nitrocellulose (NC)/LiFSI electrolyte is developed to realize highly reversible Li deposition/dissolution. This unique electrolyte enables Li metal batteries to demonstrate remarkable electrochemical performance, i.e., stable operation under high current density up to 10 mA cm −2 . Moreover, Li|LiFePO4 (LFP) pouch cells with 2m FM+2% NC electrolytes achieve almost 100% capacity retention after 210 cycles under a limited environment.